Amplification and clinicopathological significance of HER-2 in Kazakh esophageal squamous cell carcinoma - Muhetaer, Aishanjiang (Mol Clin Oncol, 2020)
Amplification and overexpression of the human epidermal growth factor receptor-2 (HER-2) gene accelerates cell division and proliferation, and promotes tumor growth and metastasis in various malignant tumors. However, there are few reports on its influence and mechanism in esophageal cancer. The aim of the present study was to investigate the gene amplification and clinicopathological significance of HER-2 in Kazakh esophageal squamous cell carcinoma (ESCC). HER-2 gene amplification was detected in 70 esophageal cancer tissues using fluorescence in situ hybridization. The association between the HER-2 gene amplification and the clinicopathological characteristics of patients with esophageal cancer was also analyzed. The amplification rate of the HER-2 gene in patients with esophageal cancer was 54.2% (38/70). The results also revealed a positive association between the amplification rate of the HER-2 gene in esophageal squamous cell carcinomas and the level of tissue differentiation, increasing gradually and significantly among the highly, moderately and poorly differentiated tissues (P<0.05). The amplification rate of the HER-2 gene in patients with lymph node metastasis was higher than those without (P<0.05). There was no significant association between the amplification rate of the HER-2 gene and any of the clinic pathological parameters, such as sex, age, depth of invasion and 3-year survival, among patients (P>0.05). In conclusion, the amplification rate of the HER-2 gene in patients with Kazakh ESCC was high. There was an association with various prognostic factors, including cancer differentiation and lymph node metastasis. HER-2 gene expression levels may be considered as an indicator of poor prognosis in patients with ESCC in the clinical setting, and this may provide a basis of treatment for individualized targeted therapies.